Multi-level analysis of value creation in supply chain management: evidence from New Zealand clusters - Wood, Lincoln (IEOM Research Solutions Pty Ltd, 2010)
Supply chain management research frequently proceeds with little attention to the level of analysis being undertaken. Drawing from evidence from New Zealand clusters, the importance of analysis and understanding at different levels is demonstrated. In seeking to understand the role of clusters in value creation in supply chains, the capabilities present in the clusters are investigated. The analysis shows that individuals, firms, and the cluster levels are important in determining the capabilities that are leveraged by the cluster in generating value within the supply chain.